Caso hematológico: hemorragia tardia pós adeno-amigdalectomia - Salgado, M. (2011)
The authors present the clinical case of a six years old child followed by Pediatric Hematology because of anemia detected after a late hemorrhage following adenotonsillectomy, debating the differential diagnosis and management.